(untitled) (Malaysian Journal of Civil Engineering, 2018)
Floods hit various states in Malaysia and caused damage to properties, infrastructures, human suffering and even loss of lives. Frequent flood incidents and soil erosion are reported which lead to sedimentation problems in the drainage and river systems due to urbanisation. It is important to understand the sedimentation process and the behaviour of bed forms in the water course for post-flood events. However, it is risky and dangerous to conduct field study during occurrence of flooding. Laboratory study has been chosen as an alternative to fulfill the objectives. Experimental investigations on the bed load transport and bed forms in rectangular open channels have been undertaken. Small and large scale physical models are used in the laboratory. The effects of flow on mobile sandy bed channel and bed load transportation are studied by using a modified flumes with an asymmetric straight compound channel. However, the findings on rate of transport and bed formation for non-flooding cases are presented in this paper. It is found that the bed formation profiles for both channels are different due to scale and flume characteristics. The bed forms, erosion and deposition processes are significantly influenced by the water velocity in the channel. The bed forms observed for large flume are repeating ripples and dunes; meanwhile variable of ripples are observed in small flume.